Three Mistakes We Have Made During Fabrication of Quantum Dots Solar Cell; How Can You Learn From Them - Saifful Kamaluddin, Muzakir; Roslan, Umar (Centre for Ionics Universiti of Malaya (CIUM), 2017)
Solar cells are in focus for decades due to their capability to convert solar energy into electrical energy. Quantum dots sensitized solar cell (QDSC) gained much consideration due to their relatively simpler device structure and similarity to dye sensitized solar cell (DSSC). QDs are capable of delivering multiple electron per absorbed photon of sufficient energy, a phenomenon known as multi-exciton generation (MEG). The MEG effect makes QDSCs capable of achieving photovoltaics conversion efficiency (PCE) as high as 60%. Regardless of the outstanding feature of QDs, QDSCs deliver much inferior practical PCE (~8.6 %) compared to DSSCs (~13%). Density functional theory (DFT) calculations was engaged to shed some light on the problem in our previous work. Realistic QDs models were empirically developed using DFT and experimental results. Three parameters were concluded to have distinct effects on the photovoltaic (PV) properties of QDSCs. They are (i) the best size of QDs, (ii) ligand usage, and (iii) QDs size distribution; which commonly neglected by researchers. In this work, quantum dots – metal oxide semiconductor (MOS) conjugates were chemically developed; spectroscopically demonstrate various electron injection efficiency from QDs to MOS.